2007
DOI: 10.1159/000101731
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Psychological and Personality Features Related to Age of Onset of Anorexia Nervosa

Abstract: Background: To investigate the relationship between age of onset and clinical and personality features of patients with anorexia nervosa (AN). Sampling andMethod: We assessed 250 outpatients with AN with the Temperament and Character Inventory, the Eating Disorder Inventory 2, the Beck Depression Inventory and the Body Shape Questionnaire. The patients were subdivided into 3 groups: early (n = 73), intermediate (n = 96) and late onset (n = 81), based on age of onset of symptoms. Results: The early-onset group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 67 publications
6
17
1
Order By: Relevance
“…Recently, several lines of evidence have shown that the age at onset for ED is decreasing compared with a few decades ago (Favaro, Caregaro, Tenconi, Bosello, & Santonastaso, ; Matsumoto et al, ; Volpe et al, ). Such precession of age at onset does not seem to be a random phenomenon, as it is related to specific clinical and psychological features and to a less favourable course (Abbate‐Daga et al, ). Clearly, in those cases, a longer time needed to reach specialist ED care may imply the risk of higher degrees of chronicity and a worse outcome (Broomfield, Stedal, Touyz, & Rhodes, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several lines of evidence have shown that the age at onset for ED is decreasing compared with a few decades ago (Favaro, Caregaro, Tenconi, Bosello, & Santonastaso, ; Matsumoto et al, ; Volpe et al, ). Such precession of age at onset does not seem to be a random phenomenon, as it is related to specific clinical and psychological features and to a less favourable course (Abbate‐Daga et al, ). Clearly, in those cases, a longer time needed to reach specialist ED care may imply the risk of higher degrees of chronicity and a worse outcome (Broomfield, Stedal, Touyz, & Rhodes, ).…”
Section: Discussionmentioning
confidence: 99%
“…The finding that reported eating disorder pathology is equivalent in both EO‐AN and AO‐AN is in line with reports in previous literature (Cooper, Watkins, Bryant‐Waugh, & Lask, ). Our finding of similar body‐image distortion in both groups contradicts previous studies showing either less (de Castro & Goldstein, ) or more severe (Abbate‐Daga et al, ) body‐image distortion in EO‐AN. It should be noted that in the current study, body‐image distortion was measured via self‐report.…”
Section: Discussionmentioning
confidence: 99%
“…However, available data across age groups (Cumella and Kally, 2008) also indicate a declining trend. Comparable studies have reported that earlier age of onset chronically impedes sexual functioning and libido (Pinheiro et al, 2010); reduces the likelihood of a more positive long-term outcome (Wentz et al, 2009); and, in general, implies more personality problems, a more profound body dissatisfaction, and a longer-lasting ascetic-driven pursuit of thinness (Abbate-Daga et al, 2007). An early debut may thus be a sizeable risk factor of developing an additional PD.…”
Section: Moderator Analysesmentioning
confidence: 99%